Condom use among antiretroviral therapy patients in Ibadan, Nigeria (2010)
Background: While antiretroviral treatment (ART) has improved the health status of people living with HIV, new challenges to their sexual and reproductive health (SRH) needs and their ability to prevent secondary HIV infections have risen. This study aimed to determine the level and factors that affect condom use among ART-experienced patients at the premier teaching hospital in Nigeria. Methodology: This longitudinal study involved patients who initiated treatment at the University College Hospital, Ibadan, Nigeria, between January and December 2006. Sexually active patients who had received treatment for at least six months and had not defaulted on clinic follow-up schedules were studied. Data on socio-demographic characteristics and condom use were extracted from clinic records. Chi square test and logistic regression were employed to determine factors associated with condom use. Results: The study involved 866 patients, specifically, 306 (35.3%) men and 560 (64.7%) women aged 40.7 (SD 7.6) and 33.3 (SD 6.5) years respectively. Condoms usage before treatment and at last clinic visits was 14.0% and 43.3% respectively. Overall reports of condom use at specified periods were as follows: 1 – 6 months (33.0%); 7 – 12 months (37.3%) and above 12 months (53.8%). Patients in a marital union and those with higher education were more likely to use condoms. Conclusions: Condom use is significantly influenced by marital status and educational level. Although condom use increases together with follow-up time, the level can be improved. Primary and secondary prevention efforts targeting high-risk sexual behaviour among ART patients need to receive greater and continual attention.